Harry Potter and the prisoner of Azkaban - Rowling, J. K. (London : Bloomsbury, 2014)
During his third year at Hogwarts School of Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
"Year 3"--Spine.
Sequel to: Harry Potter and the Chamber of Secrets.
6.9
5-8.
5-8
Keywords: Fantasy; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Schools -- Fiction; Wizards -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictional character) -- Fiction; School stories; Wizards -- Fiction; England -- Fiction; England -- Fiction; Fantastic fiction